Pengaruh Pratanak Kacang Kapri (Pisum sativum axiphium L) Terhadap Kadar Serat Pangan dan Pati Resisten serta Sifat Hipoglikemiknya Pada Tikus Diabetik Induksi Alloksan - , Fitriana Mustikaningrum; , Prof. Dr. Ir. Y. Marsono ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Peas (Pisum sativum axiphium L) has been known to have hypoglycemic effect. Dietary fiber and resistant starch maybe give contribution to the properties. However, preparation of peas with conventional processing (soaking and boilling) is very time consuming and the product still have a hard texture. The aims of the study were: (a) to determine the best pre-cooking process of peas based on physical properties (texture and rehydration rate), (b) to determine effect of pre-cooking on sensories properties, (c) to determine effect of precooking on dietary fiber (soluble fiber, insoluble fiber, total fiber), resistant starch content and (d) to determine of pre-cooking peas consumption on glucose serum concentration in diabetic rat. The study was devided into two steps. The first step is determination of the best condition for pre-cooking i.e soaking solution (NaHCO3, Na2CO3, (NH4)2CO3) and autoclaving time (130s, 135s, 140s, 145s), based on physical properties of the pre-cooked bean including expansion rate and rehydration rate. The second step is bioassay for determining the hypoglycemic properties of peas bean in rats. It was found that precooked peas soaked in NaHCO3 solution. 4,2% (b/v) for 8 hours and pre-cooked in autoclave at 121 o C for 145 seconds resulted in best physical properties. The pre-cooked peas bean has higher preference in sensory properties (texture, taste, aroma and general acceptance) compered with convensional boiled. Pre-cooking increased insoluble fiber, total fiber, and resistant starch of peas. Diet containing 20 % of total energy from pre-cooked peas decreased the serum glucose of diabetic rats by 65,58% compared to 59,33% for conventional boiled peas while the control diet had no effect on the reduction of serum glucose concentration.